Synthesis of a two-dimensional layered Sm-MOF and its composite for separation and catalysis of water pollutants

By combining Sm-based coordination polymer material and composite catalyst, the problems of poor dye adsorption selectivity and insufficient catalyst stability in the prior art are solved, and efficient removal and catalyzing of organic dyes and phenolic compounds are achieved.

CN115957818BActive Publication Date: 2025-02-07LIAOCHENG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211411882.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-11
Publication Date
2025-02-07
Estimated Expiration
2042-11-11

AI Technical Summary

Technical Problem

In the prior art, when removing organic dyes and phenolic compounds from industrial wastewater, there are problems such as poor adsorption selectivity, low adsorption amount, and thermal instability of the catalyst.

Method used

A Sm-based coordination polymer material and its composite catalyst were developed to separate cationic dyes by physical adsorption, and the reduction of nitrophenol compounds was catalyzed using the Sm-based composite catalyst.

Benefits of technology

It realizes efficient adsorption and separation of cationic dyes, has good stability and recycling capabilities, and improves catalytic activity and can quickly remove nitrophenol compounds in the liquid phase.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115957818B_ABST
    Figure CN115957818B_ABST
Patent Text Reader

Abstract

A two-dimensional layered Sm-MOF is synthesized and its composite is used for separation and catalysis of water pollutants. SmCl3·6H2O is added to secondary water, 5-[(anthracene-9-methylene)amino]-isophthalic acid (H2AAPA) is added to N,N-dimethylacetamide (DMA), and the two solvents are mixed and placed in a high-pressure reactor for hydrothermal reaction to generate Sm-based coordination polymers [Sm4(AAPA)6(DMA)2(H2O)4][(DMA)3(H2O)8]. The Sm-based coordination polymer can adsorb methylene blue and rhodamine B (the adsorption amounts are 0.97 g·g ‑1 and 0.41 g·g ‑1 ), methyl orange is separated, and it has good reusability. The Sm-based coordination polymer is dispersed in a methanol solution as a carrier, PdCl2 is added and stirred overnight, NaBH4 is added and stirred continuously, solid is separated by centrifugation, and a Sm-based composite catalyst is obtained by vacuum drying. In the Sm-based composite catalyst, Pd NPs are highly uniformly dispersed in the carrier, the catalytic activity is improved, and the nitrophenol compounds in the liquid phase can be quickly removed as a heterogeneous catalyst. The above material can be used as a physical adsorbent for organic dyes and a scavenger for nitrophenol compounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water pollutant separation and catalysis, and specifically relates to a preparation method of a Sm-based coordination polymer material and a composite catalyst thereof, and application thereof in dye adsorption separation and catalysis of nitrophenol compounds. Background Art

[0002] Metal-organic frameworks (MOFs), also known as porous coordination polymers, are a type of crystalline porous materials. MOFs porous materials contain abundant pores and have good performance in the fields of adsorption separation, fluorescence sensing, catalysis, magnetism, etc., and have received widespread attention. This type of material is a coordination polymer with a periodic network structure and regular pores, which is formed by connecting organic ligands containing carboxylic acids, phosphoric acids or nitrogen with metal ions or metal clusters through coordination bonds. The organic ligands serve as linkers, and the metal ions or metal clusters serve as nodes. The organic ligands as linkers can be modified and the length can be controlled. There are many types of metal elements that can participate in the coordination nodes, and the MOFs material structure is rich. Compared with traditional inorganic porous molecular sieves and activated carbon materials, MOFs materials have the advantages of adjustable pore size, adjustable pore surface, and multiple sites for interacting with guest molecules. By modifying or optimizing the linker or node, the adsorption separation, fluorescence sensing, catalysis, photoelectromagnetic and other properties of the material can be effectively improved.

[0003] In recent years, water pollution has become a huge environmental challenge facing mankind. Industrial pollution comes from various pollutants in the food, textile, cosmetic, rubber, drug and pharmaceutical industries, which belong to organic pollutants. 3 Among various organic wastes, dyes (i.e., MB, RhB, MO) 4 and phenolic compounds (i.e., o-nitrophenol (2-NP), m-nitrophenol (3-NP) and p-nitrophenol (4-NP)) 5 are highly toxic, highly carcinogenic and difficult to biodegrade, which have attracted widespread attention from the scientific community. Therefore, it is crucial to adopt cost-effective strategies to effectively remove the above pollutants from industrial wastewater. Currently, a large number of methods are used to remove organic dyes from wastewater, such as electrochemical degradation, photolysis, physical adsorption, chemical adsorption, reverse osmosis, biological method, chemical precipitation, etc. Considering factors such as selectivity, efficiency and cost, physical adsorption is one of the best methods for removing organic dyes from wastewater. However, commercial and traditional adsorbents have many disadvantages, such as poor adsorption selectivity and low adsorption capacity, which limit their application in the separation and purification of dyes. Therefore, it is necessary to synthesize a functional material adsorbent with high selectivity for dyes. Nitrophenols are difficult to remove due to their high water solubility and environmental stability. 4-NP is a "priority pollutant" that is widely present in agricultural and chemical wastewater. However, 4-aminophenol (4-AP), as the reduction product of 4-NP, is an important organic chemical intermediate that can be widely used in many industrial processes. For example, 4-AP is used as an intermediate in the synthesis of photographic developers, drugs such as analgesics, and fine chemicals. Reduction of 4-NP to 4-AP is an effective method, and the conversion of 4-NP under mild conditions can be achieved using metal nanoparticles (MNPs). Compared with other MNPs, palladium nanoparticles (Pd NPs) show superior catalytic activity. However, Pd NPs are thermally unstable during the reaction and easily aggregate into different nanostructures, resulting in a significant decrease in their activity. In order to prevent their agglomeration, the development of suitable supports or stabilizers is urgently needed. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a preparation method of a Sm-based coordination polymer material and a composite catalyst thereof and their application in dye adsorption separation and catalysis of nitrophenol compounds. The chemical formula of the coordination polymer material is [Sm4(AAPA)6(DMA)2(H2O)4][(DMA)3(H2O)8], and the crystal form of the porous material of the coordination polymer material belongs to the triclinic system, the space group is P-1, and the unit cell parameters are: The coordination polymer synthesized in the present invention can adsorb cationic dyes MB and RhB in water by physical adsorption, and repel anionic dye MO, and has a high adsorption capacity for MB and RhB, which are 0.97 g·g-1 and 0.41 g·g -1 ; In addition, the coordination polymer of the present invention can be recycled, has good stability for dyes MB and RhB, can be used as a physical adsorbent to adsorb cationic dyes in water and separate anionic dyes, and has good application prospects. The Sm-based coordination polymer material is used as a carrier to load palladium nanoparticles to prepare the Sm-based composite catalyst of the present invention. In the composite catalyst of the present invention, Pd NPs are highly uniformly dispersed in the carrier, which improves the catalytic activity of the Sm-based composite catalyst of the present invention, and can be used as a heterogeneous catalyst to quickly remove nitrophenol compounds in the liquid phase.

[0005] The first aspect of the present invention provides a coordination polymer material and a composite catalyst thereof, wherein the chemical formula of the coordination polymer material is [Sm4(AAPA)6(DMA)2(H2O)4][(DMA)3(H2O)8], wherein AAPA represents a deprotonated 5-[(anthracene-9-methylene)amino]-isophthalic acid ligand, and DMA represents N,N-dimethylacetamide; the Sm-based composite catalyst uses the Sm-based coordination polymer material as a carrier to load palladium nanoparticles.

[0006] According to the first aspect of the present invention, in some embodiments of the present invention, the crystal form of the coordination polymer material belongs to the triclinic system, the space group is P-1, and the unit cell parameters are:

[0007] The coordination polymer of the present invention is a two-dimensional layered structure material with a one-dimensional network formed by connecting deprotonated AAPA with a tetranuclear Sm cluster. The tetranuclear Sm cluster unit is composed of two different Sm dimers (Sm1-Sm2, Sm3-Sm4), each of which is composed of two Sm (III) atoms independent of the crystal. In a dimer Sm1-Sm2, the Sm1 center is coordinated with eight carboxylic acid oxygen atoms from five different deprotonated AAPA ligands and shows a distorted dodecahedral geometry; the Sm2 center is also eight-coordinated, coordinated with five carboxylic acid oxygen atoms from four different deprotonated AAPA ligands, one DMA oxygen atom and two oxygen atoms from water molecules, and the distance between Sm1 and Sm2 is In the other dimer Sm3-Sm4, the Sm3 center is similar to Sm1, coordinated with eight carboxylic acid oxygen atoms, showing a distorted dodecahedral geometry, and the Sm4 center is similar to Sm2, coordinated with five carboxylic acid oxygen atoms, one DMA oxygen atom, and two water oxygen atoms. The distance between Sm3 and Sm4 is Two different binuclear metal clusters via AAPA 2-The connections of the ligands continue to extend outward to form a two-dimensional layered structure.

[0008] The second aspect of the present invention provides a method for preparing the coordination polymer material and its composite catalyst described in the first aspect of the present invention, wherein the coordination polymer material is prepared by reacting the ligand 5-[(anthracene-9-methylene)amino]-isophthalic acid with a samarium salt in a solvent; and the Sm-based composite catalyst is prepared by dispersing a carrier and a substance providing palladium nanoparticles in a solvent and then reducing them with a reducing agent.

[0009] In some preferred embodiments of the present invention, the solvent consists of water, N,N-dimethylacetamide and methanol.

[0010] In some preferred embodiments of the present invention, the volume ratio of water to N,N-dimethylacetamide in the solvent is (1-3):1.

[0011] In some preferred embodiments of the present invention, the molar ratio of the 5-[(anthracene-9-methylene)amino]-isophthalic acid to the samarium salt is 1:(1-3).

[0012] In some preferred embodiments of the present invention, the samarium salt is a trivalent Sm salt.

[0013] In some more preferred embodiments of the present invention, the samarium salt is selected from at least one of SmCl3, Sm(NO3)3, Sm(CH3COO)3 and hydrates thereof.

[0014] In some more preferred embodiments of the present invention, the samarium salt is SmCl3·H2O.

[0015] In some more preferred embodiments of the present invention, the reaction temperature is 80-120° C., and the reaction time is 48 h to 96 h.

[0016] In some preferred embodiments of the present invention, 4 to 5 mg of the coordination polymer carrier is added per milliliter of solvent.

[0017] In some preferred embodiments of the present invention, the substance providing palladium nanoparticles is a palladium salt.

[0018] In some preferred embodiments of the present invention, the substance providing palladium nanoparticles is a palladium salt.

[0019] In some more preferred embodiments of the present invention, the palladium salt is selected from at least one of PdCl2, Pd(NO3)2, and Pd(CH3COO)2.

[0020] In some more preferred embodiments of the present invention, the palladium salt is PdCl2.

[0021] In some preferred embodiments of the present invention, the mass ratio of the carrier to the substance providing palladium nanoparticles is (40-60):1.

[0022] In some preferred embodiments of the present invention, the dispersion temperature is 25-35°C.

[0023] In some preferred embodiments of the present invention, the dispersion time is 4 to 6 hours.

[0024] In some preferred embodiments of the present invention, the reducing agent is sodium borohydride.

[0025] In some preferred embodiments of the present invention, stirring is continued for 1 to 2 hours after the reducing agent is added.

[0026] In some preferred embodiments of the present invention, the mass ratio of the total mass of the carrier and the material providing palladium nanoparticles to the mass ratio of the reducing agent is 1:(550-750). The third aspect of the present invention provides an application of the coordination polymer material described in the first aspect of the present invention in the adsorption of cationic organic dyes and the separation of anionic organic dyes; and an application of the composite catalyst in the preparation of nitrophenol removal products.

[0027] According to the third aspect of the present invention, in some embodiments of the present invention, the cationic organic dye includes methylene blue (MB) and rhodamine B (RhB), and the anionic organic dye includes methyl orange (MO); in some embodiments of the present invention, the nitrophenol removal product also includes a reducing agent.

[0028] In some preferred embodiments of the present invention, the reducing agent is NaBH4.

[0029] In some preferred embodiments of the present invention, the mass ratio of the Sm-based composite catalyst to the reducing agent in the nitrophenol removal product is 1:(550-750).

[0030] In some preferred embodiments of the present invention, the Sm-based composite catalyst described in the first aspect of the present invention is configured as a solution for use.

[0031] In some preferred embodiments of the present invention, the concentration of the Sm-based composite catalyst dispersion is 10 to 20 mg / mL -1 .

[0032] In some preferred embodiments of the present invention, the conversion of the nitrophenol compound can be completed by mixing the reducing agent, the Sm-based composite catalyst dispersion and the solution containing the nitrophenol compound.

[0033] The Pd NPs in the present invention are uniformly distributed in the carrier, wherein the Pd NPs are highly uniformly dispersed in the carrier [Sm4(AAPA)6(DMA)2(H2O)4][(DMA)3(H2O)8], thereby improving the catalytic activity of the reaction. After adding a reducing agent, the Sm-based composite catalyst can efficiently catalyze the reduction of nitrophenol compounds, thereby achieving the purpose of rapidly removing nitrophenol compounds in the liquid phase. In addition, since the carrier in the present invention has good stability, the Sm-based composite catalyst of the present invention has both the advantages of catalytic efficiency and cyclic stability.

[0034] The fourth aspect of the present invention provides an application of the coordination polymer material and the composite catalyst thereof described in the first aspect of the present invention in water treatment.

[0035] According to the fourth aspect of the present invention, in some embodiments of the present invention, the water treatment includes adsorption and separation of organic dyes in the water and removal of nitrophenols in the liquid phase.

[0036] In some preferred embodiments of the present invention, the organic dye includes cationic organic dye methylene blue (MB), rhodamine B (RhB), anionic organic dye methyl orange (MO); the nitrophenol substances include p-nitrophenol (4-NP), m-nitrophenol (3-NP), o-nitrophenol (2-NP).

[0037] The fifth aspect of the present invention provides a physical adsorbent and a catalyst, wherein the physical adsorbent includes the Sm-based coordination polymer material described in the first aspect of the present invention; and the catalyst includes the Sm-based composite catalyst described in the first aspect of the present invention.

[0038] The beneficial effects of the present invention are:

[0039] (1) The organic crystalline material provided by the present invention has good thermal stability and can be stable to 583K; the chemical stability is also very good. When it is immersed in an aqueous solution with a pH of 2≤≤12 for 24 hours, the framework structure of the coordination polymer of the present invention will not be destroyed;

[0040] (2) The coordination polymer material synthesized in the present invention has good thermal stability and chemical stability, and can efficiently and quickly adsorb cationic dyes MB and RhB and separate anionic dye MO in water by physical adsorption. The adsorption capacity of MB by the coordination polymer material is as high as 0.97 g·g -1 The adsorption amount of RhB was 0.41 g·g -1 In addition, the coordination polymer of the present invention can be recycled, has good stability in the adsorption and separation of cationic dyes, can be used as a physical adsorbent to adsorb and separate organic dyes in water, and has good application prospects.

[0041] (3) The present invention uses a carrier [Sm4(AAPA)6(DMA)2(H2O)4][(DMA)3(H2O)8] and Pd NPs to prepare the Sm-based composite catalyst of the present invention. The Pd NPs of the present invention are evenly distributed in the carrier, wherein the Pd NPs are highly evenly dispersed in the carrier, thereby improving the catalytic activity of the reaction. After adding a reducing agent, the Sm-based composite catalyst can efficiently catalyze the reduction of nitrophenol compounds, thereby achieving the purpose of rapidly removing nitrophenol compounds. The TOF values ​​of the catalyst for 2-NP, 3-NP and 4-NP are 0.55, 2.19 and 1.09s, respectively. -1 , and the catalyst has very good cyclic stability and has good application prospects in removing nitrophenol compounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a schematic diagram of the synthesis process of the coordination polymer in the present invention;

[0043] Figure 2 is a schematic diagram of the two-dimensional structure of the coordination polymer of the present invention;

[0044] Figure 3 is the Sm in the coordination polymer of the present invention 3+ The coordination environment diagram of

[0045] Figure 4 It is a schematic diagram of the synthesis process of the coordination polymer composite catalyst in the present invention;

[0046] Figure 5 is a thermogravimetric curve of the coordination polymer of the present invention;

[0047] Figure 6 is a polycrystalline X-ray diffraction (PXRD) diagram of the coordination polymer of the present invention after being immersed in aqueous solutions of different pH values;

[0048] Figure 7 is an infrared absorption spectrum curve of the coordination polymer of the present invention;

[0049] Figure 8 It is a PXRD simulation diagram, a PXRD diagram of the coordination polymer in the present invention and a PXRD diagram of the Sm-based composite catalyst;

[0050] Fig. 9 It is the infrared absorption spectrum of the coordination polymer and the Sm-based composite catalyst in the present invention;

[0051] Fig.10 The SEM image of the Sm-based composite catalyst of the present invention and the distribution of elements in the Sm-based composite catalyst;

[0052] Fig.11 is a transmission electron microscope image of the Sm-based composite catalyst in the present invention;

[0053] Fig.12 is the adsorption curve of MB by the coordination polymer of the present invention;

[0054] Fig.13 is the adsorption curve of RhB by the coordination polymer of the present invention;

[0055] Fig.14 is the adsorption isotherm curve of MB by the coordination polymer of the present invention;

[0056] Fig.15 is the adsorption isotherm curve of the coordination polymer of the present invention to RhB;

[0057] Fig.16 It is the cycle bar graph and powder graph of the coordination polymer of the present invention to MB and RhB;

[0058] Fig.17 is the adsorption curve of the coordination polymer MO in the present invention;

[0059] Fig.18 is the adsorption curve of the coordination polymer in the present invention selectively adsorbing MB in the MB / MO mixed dye;

[0060] Fig.19 is the adsorption curve of the coordination polymer in the present invention selectively adsorbing RhB in the RhB / MO mixed dye;

[0061] Fig. 20 The coordination polymer of the present invention is used for column chromatography to adsorb MB in the mixed dye MB / MO and separate MO;

[0062] Fig.21 The coordination polymer of the present invention is used for column chromatography to adsorb RhB in the mixed dye RhB / MO and separate MO;

[0063] Fig. 22 The UV-visible absorption spectra of o-nitrophenol solution after different catalytic times;

[0064] Fig.23 is the first-order kinetic fitting curve of the catalytic reduction of o-nitrophenol by the Sm-based composite catalyst in the present invention;

[0065] Fig.24 The UV-visible absorption spectra of m-nitrophenol solution after different catalytic times;

[0066] Fig.25is the first-order kinetic fitting curve of the catalytic reduction of m-nitrophenol by the Sm-based composite catalyst in the present invention;

[0067] Fig.26 The UV-visible absorption spectra of p-nitrophenol solution after different catalytic times;

[0068] Fig. 27 is the first-order kinetic fitting curve of the catalytic reduction of p-nitrophenol by the Sm-based composite catalyst in the present invention;

[0069] Fig.28 is the catalytic rate of the Sm-based composite catalyst of the present invention on p-nitrophenol at different temperatures;

[0070] Fig.29 is the activation energy of the catalytic reduction of p-nitrophenol by the Sm-based composite catalyst of the present invention;

[0071] Fig.30 It is the catalytic efficiency of the Sm-based composite catalyst in the present invention under different times of use. DETAILED DESCRIPTION

[0072] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, these embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.

[0073] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0074] Example Preparation of Sm Coordination Polymer and Sm-based Composite Catalyst

[0075] The preparation of the Sm coordination polymer in this embodiment comprises the following steps:

[0076] (1) 13.7 mg of 5-[(anthracene-9-methylene)amino]-isophthalic acid (H2AAPA) and 36.48 mg of SmCl3·6H2O were reacted in a solvent consisting of 2 mL of water and 3 mL of N,N-dimethylacetamide (DMA) at a temperature of 100°C for 48 h. The resulting crystals were washed three times with ethanol and then vacuum dried in a vacuum drying oven to obtain the Sm coordination polymer of this embodiment, wherein the vacuum drying temperature was 70°C and the vacuum drying time was 12 h.

[0077] The schematic diagram of the synthesis process of the Sm coordination polymer in the embodiment of the present invention is as follows Figure 1 shown.

[0078] The chemical formula of the Sm coordination polymer material prepared in the embodiment of the present invention is [Sm4(AAPA)6(DMA)2(H2O)4][(DMA)3(H2O)8], wherein DCPN represents the deprotonated 5-[(anthracene-9-methylene)amino]-isophthalic acid ligand; and DMA represents N,N-dimethylacetamide.

[0079] The coordination polymer of the present invention is a two-dimensional layered structure material with a one-dimensional network formed by connecting deprotonated AAPA with a tetranuclear Sm cluster. The tetranuclear Sm cluster unit is composed of two different Sm dimers (Sm1-Sm2, Sm3-Sm4), each of which is composed of two Sm (III) atoms independent of the crystal. In a dimer Sm1-Sm2, the Sm1 center is coordinated with eight carboxylic acid oxygen atoms from five different deprotonated AAPA ligands and shows a distorted dodecahedral geometry; the Sm2 center is also eight-coordinated, coordinated with five carboxylic acid oxygen atoms from four different deprotonated AAPA ligands, one DMA oxygen atom and two oxygen atoms from water molecules, and the distance between Sm1 and Sm2 is In the other dimer Sm3-Sm4, the Sm3 center is similar to Sm1, coordinated with eight carboxylic acid oxygen atoms, showing a distorted dodecahedral geometry, and the Sm4 center is similar to Sm2, coordinated with five carboxylic acid oxygen atoms, one DMA oxygen atom, and two water oxygen atoms. The distance between Sm3 and Sm4 is Two different binuclear metal clusters are connected by AAPA2-ligands and extend outward to form a two-dimensional layered structure. The schematic diagram of the two-dimensional structure of this coordination polymer is shown in Figure 2 As shown, Figure 3 is the Sm in the coordination polymer in the embodiment of the present invention 3+ Coordination environment diagram.

[0080] The preparation of the Sm-based composite catalyst in this embodiment comprises the following steps:

[0081] (2) 100 mg of the carrier in step (1) was dispersed in 20 mL of methanol solution, 6 mg of PdCl2 was added to the methanol solution of the carrier, and stirred for 8 h, 3 mg of NaBH4 was added to the methanol mixed solution containing the carrier and PdCl2, and stirring was continued for 4 h;

[0082] (3) The product in step (2) is vacuum dried to obtain a Sm-based composite catalyst, wherein the vacuum drying temperature is 70° C. and the vacuum drying time is 12 h.

[0083] The schematic diagram of the synthesis process of the Sm-based composite catalyst in the embodiment of the present invention is as follows Figure 4 shown.

[0084] 1. Crystallographic determination of coordination polymers

[0085] The single crystal X-ray diffraction data of the coordination polymers in the above examples were obtained using a Rigaku Oxford Diffraction Gemini diffractometer, and Cu Kα The data were collected by ω scanning, analyzed by direct method, and then the coordinates of all non-hydrogen atoms were obtained by difference Fourier function method and least square method, and finally the structure was modified by least square method. The hydrogen atoms of the coordination polymer were obtained by theoretical hydrogenation method. The calculation work was completed on PC using Olex2 program. Detailed crystal measurement data are shown in Table 1.

[0086] Table 1 Crystal determination data

[0087]

[0088] manual

[0089]

[0090] Note: a R1=∑||F0|-|F C || / ∑|F0|; b wR2=∑[w(F0 2 -F C 2 ) 2 ] / ∑[w(F0 2 ) 2 ] 1 / 2 .

[0091] It can be seen from Table 1 that the crystal form of the coordination polymer in the embodiment of the present invention belongs to the triclinic system, the space group is P-1, and the unit cell parameters are:

[0092] 2. Characterization of coordination polymers and their composite catalysts

[0093] 1. The thermal stability of the coordination polymer in the above embodiment was obtained by thermogravimetric analysis (TGA). The test temperature range was 30-750°C. The obtained thermogravimetric curve was as follows: Figure 5 As shown. Figure 5 It can be seen that the coordination polymer in the embodiment of the present invention has good thermal stability and can be stable to 583K. The good thermal stability lays a foundation for its application in the adsorption of organic dye molecules in water and also lays a foundation for it as a carrier of Pd NPs.

[0094] 2. The coordination polymers in the embodiments of the present invention were immersed in aqueous solutions with different pH values, the immersion temperature was 25°C, and the immersion time was 24 hours. Sodium hydroxide or hydrochloric acid was used to adjust the pH value of the aqueous solution. The PXRD pattern of the coordination polymer after immersion was tested using a polycrystalline X-ray diffractometer. The results are as follows: Figure 6 As shown, from Figure 6 It can be seen that after soaking in aqueous solutions of different pH values, the peaks in the PXRD diagram of the coordination polymer in the above embodiment did not change, that is, after soaking in aqueous solutions of different pH values, the structure of the coordination polymer in the above embodiment was not destroyed, indicating that it has good chemical stability in aqueous solutions of different pH values.

[0095] 3. The infrared absorption spectra of the coordination polymers in the above embodiments were obtained using an infrared absorption spectrometer, as shown in FIG. Figure 7 As shown in the figure, it can be seen that the obvious C=O (1602.07cm -1 ) and OH(3403.26cm -1 )'s stretching vibration.

[0096] 4. The PXRD pattern of the Sm-based composite catalyst prepared in the embodiment of the present invention was obtained using a polycrystalline X-ray diffractometer. The results are as follows: Figure 8 As shown, from Figure 8 It can be seen that the characteristic peaks of the PXRD simulation diagram of the carrier (based on the single crystal structure of the carrier, the PXRD diagram of the carrier is simulated by software), the PXRD diagram of the carrier in the above embodiment, and the PXRD diagram of the Sm-based composite catalyst in the above embodiment match well, indicating that the Pd NPs are accurately encapsulated into the carrier, and after the Pd NPs enter the carrier, the skeleton structure of the carrier is not changed. And because the content of Pd NPs is low, the characteristic peaks of Pd NPs do not appear in the PXRD diagram of the Sm-based composite catalyst.

[0097] 5. The infrared absorption spectra of the carrier and the Sm-based composite catalyst in the above embodiment were obtained using an infrared spectrometer. The results are as follows: Fig. 9 As shown, from Fig. 9 It can be seen that after the carrier in the embodiment of the present invention is loaded with Pd NPs, the carbonyl peak shifts and the amino peak becomes significant, which indicates that the interaction sites between Pd NPs and the skeleton may be the carboxyl and amino groups in the carrier.

[0098] 6. The SEM images of the Sm-based composite catalyst in the above embodiment and the distribution of elements in the Sm-based composite catalyst were obtained using a scanning electron microscope (SEM). Fig.10 As shown, Fig.10 a is a SEM image of the Sm-based composite catalyst in the embodiment of the present invention, Fig.10 It can be seen from a that the Sm-based composite catalyst in the embodiment of the present invention is a monodisperse with a particle size of 6.0 to 16.0 μm. Fig.10 b~10f are the element distributions in the Sm-based composite catalysts in the examples of the present invention ( Fig.10 b is the distribution of C element in Sm-based composite catalyst, Fig.10 c is the distribution of O element in Sm-based composite catalyst, Fig.10 d is the distribution of Pd element in Sm-based composite catalyst, Fig.10 e is the distribution of N element in the Sm-based composite catalyst, Fig.10 f is the distribution of Sm element in the Sm-based composite catalyst). It can be seen from the figure that in the Sm-based composite catalyst, C, N, O, Pd, and Sm are completely uniformly and continuously dispersed in the entire sample, indicating that Pd NPs are highly uniformly distributed in the carrier.

[0099] 7. A transmission electron microscope image of the Sm-based composite catalyst in the above embodiment was obtained using a high-resolution transmission microscope. The results are as follows: Fig.11 As shown, from Fig.11 As can be seen in a, the size of Pd NPs is about 2nm to about 4nm, distributed between the layers and on the surface of the carrier. The particle size and interplanar spacing of Pd NPs on the surface of the carrier were studied, and the results are shown in Fig.11 As shown in b, from Fig.11 As can be seen in b, Pd NPs are clusters with a diameter of about 2.0 to 4.0 nm and a lattice spacing of 0.224 nm, which is consistent with the 0 Overall, the Pd NPs are evenly distributed in the support with an average particle size of 3.0 nm.

[0100] 8. The mass percentage of Pd in ​​the Sm-based composite catalyst in the above example was measured by inductively coupled plasma-mass spectrometry (ICP-MS) to be 0.67 wt%.

[0101] Application Example 1 Adsorption of cationic dyes (MB and RhB) in water

[0102] The coordination polymer (20mg) in the above-described embodiment is fully ground and is dispersed in the aqueous solution of 20mL organic dye MB and RhB respectively, wherein the concentration of the organic dye is 10ppm. Then, at a certain time interval, 3mL mixed solution is taken out from the reaction mixture, centrifuged, and the solid coordination polymer adsorbent is separated, and the supernatant is taken and carried out UV-visible spectrum research, and the remaining solid coordination polymer adsorbent is poured back in the reaction system. After fast UV-visible spectrum measurement, the solution recovered is returned to the reaction mixture immediately.

[0103] The UV-visible spectra during the test were obtained using a UV-visible spectrophotometer. Fig.12 , as shown in 13, the coordination polymer in the above embodiment has an effect on the organic dye MB ( Fig.12 ) and RhB( Fig.13 ) showed good adsorption behavior in aqueous solution and could be basically adsorbed completely within 90 min. In addition, the maximum adsorption capacity of MB and RhB was calculated to be 0.97 g·g by fitting the Langmuir adsorption isotherm. -1 ( Fig.14 ) and 0.41 g·g -1 ( Fig.15 ), so the coordination polymer in the above embodiment has a high selectivity and a large adsorption capacity for MB. In addition, after the coordination polymer in the above embodiment was subjected to four cycles of adsorption and desorption of organic dyes MB and RhB, it was found that it still had a high adsorption performance, indicating that the material has good cyclic stability ( Fig.16 ).

[0104] Application Example 2 Selective adsorption of MB and RhB in mixed dyes (MB / MO and RhB / MO) in water; separation of MO

[0105] We fully grind and disperse the synthesized sample (20 mg) in 20 mL of an aqueous solution of organic dye MO, wherein the concentration of the organic dye is 10 ppm. Separately, the synthesized sample (30 mg) is fully grinded and dispersed in 30 mL of an aqueous solution of organic mixed dyes (MB / MO and RhB / MO). Then, at certain time intervals, 3 mL of the mixed solution is taken out from the reaction mixture, centrifuged, the solid adsorbent is separated, the supernatant is taken for UV-visible spectroscopy study, and the remaining solid adsorbent is poured back into the reaction system. After a rapid UV-visible spectroscopy measurement, the recovered solution is immediately returned to the reaction mixture.

[0106] like Fig.17 As shown in the figure, the crystalline material basically does not adsorb the organic dye MO in aqueous solution. In addition, the crystalline material can selectively adsorb the cationic dye MB in aqueous solutions of organic mixed dyes MB / MO (1:1) and RhB / MO (1:1). Fig.18 ) and RhB( Fig.19 ) to separate the anionic dye MO. In order to further verify the selective adsorption ability of the crystalline material, a column chromatography filter with a height of 3 cm was used for separation. After adding the mixed dye aqueous solution to the above chromatographic column, MO was quickly eluted, and MB ( Fig. 20 ) or RhB( Fig.21) are captured on the column. According to the above experimental results, the crystalline material is an excellent column chromatography filter for separating dye molecules, and may also become a potential adsorbent for recovering MB or RhB in actual industrial production.

[0107] Application Example 3 Catalytic Effect on 2-nitrophenol (2-NP)

[0108] Add 3.0 mL of light yellow 2-NP methanol solution (10 -4 M). Then, 3 mg of fresh NaBH4 solid was added to the aqueous solution. Then, 10 μL of the methanol dispersion of the Sm-based composite catalyst in the embodiment of the present invention (15 mg mL -1 ) was added to the above light yellow solution. The conversion process of 2-NP to 2-AP was detected by UV-visible spectrophotometry. The UV-visible absorption spectra of the 2-NP solution after different catalytic times were tested. The results are as follows Fig. 22 As shown, from Fig. 22 It can be seen that under the catalysis of the Sm-based composite catalyst in the embodiment of the present invention, it takes 2.5 minutes for 2-NP to be completely converted into 2-AP, and the conversion rate is 97%. The above results show that the Sm-based composite catalyst in the embodiment of the present invention exhibits good catalytic performance for 2-NP. Fig.23 is the first-order kinetic fitting curve of the catalytic reduction of 2-NP by the Sm-based composite catalyst in the present invention, from Fig.23 It can be seen that the apparent rate constant (k) of the catalytic reduction of 2-NP by the Sm-based composite catalyst in the embodiment of the present invention is 1.53 min -1 At the same time, the turnover frequency (TOF) value of 2-NP catalyzed by the Sm-based composite catalyst was 0.55s -1 .

[0109]

[0110] in,

[0111] Application Example 4 Catalytic Effect on m-nitrophenol (3-NP)

[0112] Add 3.0 mL of light yellow 3-NP methanol solution (6 × 10 -4 M). Then, 3 mg of fresh NaBH4 solid was added to the aqueous solution. Then, 5 μL of the methanol dispersion of the Sm-based composite catalyst in the embodiment of the present invention (15 mg mL -1 ) was added to the above light yellow solution. The conversion process of 3-NP to 3-AP was detected by UV-visible spectrophotometry. The UV-visible absorption spectra of 3-NP solutions after different catalytic times were tested. The results are as follows: Fig.24 As shown, from Fig.24It can be seen that under the catalysis of the Sm-based composite catalyst in the embodiment of the present invention, it takes 1.5 minutes for 3-NP to be completely converted into 3-AP, and the conversion rate is 99%. The above results show that the Sm-based composite catalyst in the embodiment of the present invention exhibits good catalytic performance for 3-NP. Fig.25 is the first-order kinetic fitting curve of the catalytic reduction of 3-NP by the Sm-based composite catalyst in the present invention, from Fig.25 It can be seen that the apparent rate constant (k) of the catalytic reduction of 3-NP by the Sm-based composite catalyst in the embodiment of the present invention is 2.66 min -1 At the same time, the turnover frequency (TOF) value of 3-NP catalyzed by the Sm-based composite catalyst was 2.19s -1 .

[0113] The calculation method of conversion rate and TOF is the same as that of Application Example 3.

[0114] Application Example 5 Catalytic Effect on p-Nitrophenol (4-NP)

[0115] Add 3.0 mL of light yellow 4-NP methanol solution (10 -4 M). Then, 3 mg of fresh NaBH4 solid was added to the aqueous solution. Then, 20 μL of the methanol dispersion of the Sm-based composite catalyst in the embodiment of the present invention (15 mg mL -1 ) was added to the above light yellow solution. The conversion process of 4-NP to 4-AP was detected by UV-visible spectrophotometry. The UV-visible absorption spectra of 4-NP solutions after different catalytic times were tested. The results are as follows: Fig.26 As shown, from Fig.26 It can be seen that under the catalysis of the Sm-based composite catalyst in the embodiment of the present invention, it takes 2.0 min for 4-NP to be completely converted into 4-AP, and the conversion rate is 99%. The above results show that the Sm-based composite catalyst in the embodiment of the present invention exhibits good catalytic performance for 4-NP. Fig. 27 is the first-order kinetic fitting curve of the catalytic reduction of 4-NP by the Sm-based composite catalyst in the present invention, from Fig. 27 It can be seen that the apparent rate constant (k) of the catalytic reduction of 4-NP by the Sm-based composite catalyst in the embodiment of the present invention is 2.17 min -1 At the same time, the turnover frequency (TOF) value of 4-NP catalyzed by the Sm-based composite catalyst was 1.09s -1 .

[0116] The calculation method of conversion rate and TOF is the same as that of Application Example 3.

[0117] The catalytic effect of the Sm-based composite catalyst in the embodiment of the present invention on 4-NP at different temperatures was further tested. The catalytic rate of the Sm-based composite catalyst in the embodiment of the present invention on 4-NP at different temperatures was as follows: Fig.28 As shown, the activation energy of catalytic reduction of 4-NP by the Sm-based composite catalyst in the embodiment of the present invention was obtained by fitting the reaction rate. The result is as follows Fig.29 As shown, from Fig.29 It can be seen that the activation energy E of the Sm-based composite catalyst for catalytic reduction of 4-NP in the embodiment of the present invention is a =50.2 kJ·mol -1 . In addition, the Sm-based composite catalyst in the embodiment of the present invention has good catalytic stability. The catalytic efficiency of the Sm-based composite catalyst in the embodiment of the present invention without using the number of times is statistically analyzed. Since the amount of the composite catalyst in the embodiment of the present invention is small, the composite catalyst after use cannot be obtained by centrifugation. Therefore, after the first cycle, a high concentration of 4-NP dispersion (30mM, 0.01mL) and NaBH4 solid (3.0mg) are added to the reaction system to restore the concentrations of 4-NP and NaBH4 to the initial state of the first reaction, and then the progress of the catalytic reaction is judged by the change of the ultraviolet absorption spectrum over time. The determination method for the third and fourth times is similar to that for the second time. The results are as follows: Fig.30 As shown, from Fig.30 It can be seen that after four cycles of catalysis, the catalytic efficiency of the Sm-based composite catalyst in the embodiment of the present invention only decreases by 4.6%, indicating that the Sm-based composite catalyst in the embodiment of the present invention has good catalytic stability.

[0118] Comparative Example

[0119] The catalytic effect of commercial Pd / C (5wt%, purchased from McLean, model number: McLean P821216) catalyst was studied using the methods in Application Examples 3, 4, and 5. The catalytic rates are shown in Table 2. The results show that the k values ​​of Pd / C (5wt%) catalyzing 2-NP, 3-NP, and 4-NP are 0.14min, -1 、0.21min -1、 0.11min -1 , which values ​​are 1 / 11, 1 / 13, and 1 / 20 of the Sm-based composite catalyst in the embodiment of the present invention, respectively. The above results show that the Sm-based composite catalyst in the embodiment of the present invention has a good catalytic effect on the conversion of 2-NP, 3-NP, and 4-NP.

[0120] Table 2 Catalytic rates of Pd@Sm-MOF and Pd / C (5wt%) on 2-NP, 3-NP, and 4-NP

[0121] sample <![CDATA[2-NP(min -1 )]]> <![CDATA[3-NP(min -1 )]]> <![CDATA[4-NP(min -1 )]]> Pd@Sm-MOF 1.53 2.66 2.17 Pd / C (5wt%) 0.14 0.21 0.11

[0122] The coordination polymer of the embodiment of the present invention has good thermal stability and chemical stability, and as a selective adsorbent, it adsorbs organic cationic dyes MB and RhB in water by physical adsorption, and separates organic anionic dye MO. It has a large adsorption capacity, good selectivity, and good cyclic stability. In addition, the synthesis steps of the coordination polymer are simple and the raw materials are easily available.

[0123] The Sm-based composite catalyst in the embodiment of the present invention has a good catalytic effect on 2-NP, 3-NP, and 4-NP. This is because the Pd NPs in the present invention are highly uniformly dispersed in the carrier, which improves the catalytic activity of the reaction. After adding the reducing agent, the Sm-based composite catalyst can efficiently catalyze the reduction of nitrophenol compounds, thereby achieving the purpose of quickly removing nitrophenol compounds.

[0124] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A Sm-based coordination polymer material, characterized in that: The chemical formula of the Sm-based coordination polymer material is [Sm4(AAPA)6(DMA)2(H2O)4][(DMA)3(H2O)8], wherein AAPA represents a deprotonated 5-[(anthracene-9-methylene)amino]-isophthalic acid ligand, and DMA represents N,N-dimethylacetamide. The Sm-based coordination polymer material is a two-dimensional layered structural material formed by connecting H2AAPA with a tetranuclear Sm cluster. The crystal form of the coordination polymer material belongs to the triclinic system, the space group is P-1, and the unit cell parameters are:

2. The composite catalyst of the Sm-based coordination polymer material according to claim 1, characterized in that: Sm-based coordination polymer materials are used as carriers to load palladium nanoparticles.

3. The method for preparing the Sm-based coordination polymer material according to claim 1, characterized in that: The Sm-based coordination polymer material is prepared by reacting a ligand 5-[(anthracene-9-methylene)amino]-isophthalic acid with a samarium salt in a solvent, wherein the molar ratio of the 5-[(anthracene-9-methylene)amino]-isophthalic acid to the samarium salt is 1:(1-3), the required solvent is a mixed solution of N,N-dimethylacetamide and water, the reaction temperature is 80°C-120°C, and the reaction time is 48h-96h.

4. The method for preparing a composite catalyst of a coordination polymer material as described in claim 2, wherein the carrier and a substance providing palladium nanoparticles are dispersed in a solvent and then reduced with a reducing agent to obtain the catalyst, wherein the mass ratio of the carrier to the substance providing palladium nanoparticles is (40-60):1, the required solvent is methanol, the reaction temperature is room temperature, and the reaction time is 12h-24h.

5. The preparation method according to claim 3, characterized in that: The samarium salt is selected from at least one of SmCl3, Sm(NO3)3, Sm(CH3COO)3 and hydrates thereof.

6. The preparation method according to claim 4, characterized in that: The substance providing palladium nanoparticles is selected from at least one of PdCl2, Pd(NO3)2, and Pd(CH3COO)2.

7. The use of the Sm-based coordination polymer material according to claim 1 in the adsorption and separation of organic dyes, characterized in that: The organic dye is one of methylene blue (MB), rhodamine B (RhB) or methyl orange (MO).

Citation Information

Patent Citations

  • Rare earth metal-organic framework crystal material and preparation method and application thereof

    CN115044052A

  • Co-based composite catalyst and preparation method and application thereof

    CN115283016A